2017
DOI: 10.1016/j.jwb.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organizational separation on individuals’ knowledge sharing in MNCs

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 79 publications
(154 reference statements)
0
38
1
Order By: Relevance
“…Intrafirm knowledge exchanges across borders can be considered risky, in view of uncertainties linked to their outcomes (e.g. loss of proprietary knowledge) (Dasí, Pedersen, Gooderham, Elter, & Hildrum, 2017). As such, we consider a psychologically safe climate to be a crucial motivational factor impacting the subsidiary's attitude toward engaging in learning and using knowledge developed by the headquarters, and openly transferring knowledge to them.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Intrafirm knowledge exchanges across borders can be considered risky, in view of uncertainties linked to their outcomes (e.g. loss of proprietary knowledge) (Dasí, Pedersen, Gooderham, Elter, & Hildrum, 2017). As such, we consider a psychologically safe climate to be a crucial motivational factor impacting the subsidiary's attitude toward engaging in learning and using knowledge developed by the headquarters, and openly transferring knowledge to them.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…It is found that KS can occur at individual, group or team, and organizational levels (Alavi & Leidner, 2001;Boles, 1999;Grover & Davenport, 2001;Lam & Lambermont-Ford, 2010). For example, some studies focus on KS between individuals (e.g., Connelly & Kelloway, 2003;Dasi et al, 2017) while some focus on KS between groups or units (e.g., Hansen, 2002). Yet, some others focus on KS between organizations (e.g., Bell et al, 2002).…”
Section: Defining Knowledge Sharingmentioning
confidence: 99%
“…for organizational members to transfer and share knowledge (Lopez et al, 2004;Nonaka, 1994;Nonaka & Takeuchi, 1995) and become drivers of knowledge sharing (Dasi et al, 2017). OL induced and generated by effective KM will create organizational knowledge and such knowledge accumulation plays a key role in sustaining an organization's competitive advantage (Gao et al, 2002;Mills & Smith, 2011).…”
Section: Theoretical Framework and Propositionsmentioning
confidence: 99%
“…Institutional factors such as politico-legal (Kostova andZaheer, 1999) andsocio-cultural (Sousa andBradley, 2006) play a restraining role in the standardization and homogenization program attempts of MNEs across subsidiaries (Festing, Eidems and Royer, 2007). For example, a traditional paternalistic culture that underpins employment regulations in India (Ramaswamy, 1983) results in organizational separateness impeding the transfer of HRM practices to MNE subsidiaries (Dasi et al, 2017). The power and influence of local institutions underpins the calls for localization in HRM program development, as opposed to mimetic isomorphism (Bjorkman et al, 2008;Kostova and Roth, 2002), an argument found relevant to HRM in Asia (Schaaper et al, 2013).…”
Section: Local Obstacles To Global Hrm Practices Of Multinational Entmentioning
confidence: 99%